2023
DOI: 10.3390/ijms242115546
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis and Its Related Laboratory Biomarkers

Vittoriano Della Corte,
Federica Todaro,
Marco Cataldi
et al.

Abstract: Atherosclerosis constitutes a persistent inflammatory ailment, serving as the predominant underlying condition for coronary artery disease (CAD), peripheral artery disease (PAD), and cerebrovascular disease. The progressive buildup of plaques within the walls of medium- and large-caliber arteries characterizes the atherosclerotic process. This accumulation results in significant narrowing that impedes blood flow, leading to critical tissue oxygen deficiency. Spontaneous blockage of thrombotic vessels can preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 111 publications
(126 reference statements)
0
1
0
Order By: Relevance
“…Currently, there are several serum markers used to identify early AS, such as lipoproteins, ceramides, C-reactive proteins, high-sensitivity C-reactive proteins, matrix metalloproteinases, and miRNAs, among which high-sensitivity C-reactive proteins are comprehensively validated in the prediction of atherosclerotic cardiovascular events 45 47 . In our study, we identified six Hub genes for AS, and the nomogram demonstrated satisfactory diagnostic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are several serum markers used to identify early AS, such as lipoproteins, ceramides, C-reactive proteins, high-sensitivity C-reactive proteins, matrix metalloproteinases, and miRNAs, among which high-sensitivity C-reactive proteins are comprehensively validated in the prediction of atherosclerotic cardiovascular events 45 47 . In our study, we identified six Hub genes for AS, and the nomogram demonstrated satisfactory diagnostic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate early risk stratification could facilitate the delivery of timely treatment for patients with CAD and may improve treatment outcomes in these cases. In recent years, researchers have identified serum biomarkers that are associated with an elevated risk of atherosclerotic events [2]. Many of these biomarkers, such as lipoprotein, C-reactive protein, and others, either alone or in combination, have been integrated into risk prediction models to assess whether their inclusion improves prediction accuracy [3].…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity can decrease hs-CRP levels and CAD risk [5]. The atherosclerotic process is connected with hs-CRP, as this biomarker stimulates the uptake of LDL cholesterol into macrophages [6]. Hs-CRP is also implicated in cardiovascular outcomes [7,8].…”
Section: Introductionmentioning
confidence: 99%